Spacecraft in 'warp bubble' could travel faster than light. (July 2021) - Skuse, Benjamin
Abstract : Special relativity famously dictates that no known object can travel faster than the speed of light in a vacuum – making it unlikely that humans will ever send spacecraft to explore beyond our local area of the Milky Way. However, new research by Erik Lentz at the University of Göttingen suggests there could be a way beyond this limit.